Current developments in biotechnology and bioengineering production, isolation and purification of industrial products - Pandey, Ashok; Negi, Sangeeta; Soccol, Carlos Ricardo (Amsterdam Elsevier, 2017)
"Current Developments in Biotechnology and Bioengineering: Production, Isolation and Purification of Industrial Products provides extensive coverage of new developments, state-of-the-art technologies, and potential future trends, focusing on industrial biotechnology and bioengineering practices for the production of industrial products, such as enzymes, organic acids, biopolymers, and biosurfactants, and the processes for isolating and purifying them from a production medium. During the last few years, the tools of molecular biology and genetic and metabolic engineering have rendered tremendous improvements in the production of industrial products by fermentation. Structured by industrial product classifications, this book provides an overview of the current practice, status, and future potential for the production of these agents, along with reviews of the industrial scenario relating to their production."--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Biotechnology; Electronic books